Sport Participation in Early and Middle Adolescence: The Interplay Between Self-Perception and Psychobiosocial Experiences in Predicting Burnout Symptoms - Morano, Milena; Robazza, Claudio; Ruiz, Montse C.; Bortoli, Laura (Frontiers in Psychology, 2022)
Adolescence is characterized by pubertal physical changes, cognitive development, and modified social expectations. Adolescent athletes often enter a more challenging stage of athletic development associated with increased specialization, and become vulnerable to feelings of burnout. It is therefore important to consider intrapersonal psychological factors that can improve sport participation experiences and prevent burnout. Accordingly, the aim of the current study was to examine the interplay between self-perceptions and emotion-related (i.e., psychobiosocial) experiences (e.g., feeling confident, focused, determined, physically charged, and skillful) in predicting burnout symptoms in adolescents. A sample of 12–14-year-olds (n = 338, 176 girls and 162 boys; Mage = 13.42, SD = 1.12) and 15–17-year-olds (n = 302, 142 girls and 160 boys; Mage = 15.78, SD = 1.17), participating in individual or team sports, were involved in a cross-sectional study to assess positive and negative self-perceptions, functional and dysfunctional psychobiosocial experiences, and burnout symptoms (i.e., emotional and physical exhaustion, reduced sense of accomplishment, sport devaluation). Path analysis results suggest that higher scores on global physical self-perception, self-esteem, and sport competence were associated with lower burnout symptoms, while higher scores on social physique anxiety were associated with higher scores on sport devaluation. Moreover, self-esteem and sport competence were shown to have significant indirect effects on burnout dimensions via functional psychobiosocial experiences. Differences by gender (p < .001) and by age category (p < .001) in the variable scores were also found. Compared to girls, boys reported higher scores on competence, functional psychobiosocial experiences, global physical self-perception, self-esteem, emotional and physical exhaustion, and lower scores on social physique anxiety. Compared to 12–14-year-olds, 15–17-year-olds reported lower scores on global physical self-perception and self-esteem, and higher scores on social physique anxiety, reduced sense of accomplishment, and sport devaluation. This study adds to the literature on burnout by considering the role of intrapersonal factors (i.e., global physical self-perception, self-esteem, sport competence, and social anxiety) in predicting burnout symptoms in adolescent athletes, and the mediating effects of psychobiosocial experiences. From an applied perspective, sport coaches should implement strategies to foster positive self-perceptions, promote pleasant psychobiosocial experiences, and prevent burnout.